2021
DOI: 10.1021/acsbiomaterials.0c01719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dual Pore Size Architecture on In Vitro Osteogenic Differentiation in Additively Manufactured Hierarchical Scaffolds

Abstract: The combination of macro-and microporosity is a potent manner of enhancing osteogenic potential, but the biological events leading to this increase in osteogenesis are not well understood. In this study, we investigated the effect of a dual pore size scaffold on the physical and biological properties, with the hypothesis that cell condensation is the determining factor for enhanced osteogenic differentiation. To this end, a hierarchical scaffold possessing a dual (large and small) pore size was fabricated by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…Out of the 75 in vivo studies included, 17 evaluated the efficiency of the PCL matrix [ 32 , 35 , 37 , 50 , 51 , 52 , 53 , 54 , 55 , 62 , 63 , 65 , 66 , 73 , 77 , 81 , 120 ]. This biomaterial is the most well reviewed biomaterial in literature due to its high biocompatibility, durability and subsequent extensive use [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 75 in vivo studies included, 17 evaluated the efficiency of the PCL matrix [ 32 , 35 , 37 , 50 , 51 , 52 , 53 , 54 , 55 , 62 , 63 , 65 , 66 , 73 , 77 , 81 , 120 ]. This biomaterial is the most well reviewed biomaterial in literature due to its high biocompatibility, durability and subsequent extensive use [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shim et al reported that porosity affects osteogenesis, with matrices with 30% porosity showing better osteogenic capacity than groups with 50% and 70% porosity [ 115 ]. Regarding pore size, the literature suggests that the ideal size should be between 400 to 600 μm [ 63 , 103 , 111 ]. Finally, the pore configuration should also be considered in terms of the dynamic stability of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Small sections of freeze-dried polymeric scaffolds (PVA-PDA, PVA-l-PDA) were taken and sputter-coated with gold using a sputtering unit. The pore sizes and porosity were estimated by analyzing the SEM images using the ImageJ program. …”
Section: Materials and Methodologymentioning
confidence: 99%
“…Further proof that the PHBV/ CaSH/CS scaffold might successfully encourage the development of new bone came from in vivo investigations. Ratheesh et al [ 110 ] prepared a double pore size layered scaffold using polycaprolactone (PCL) in combination with melt electrowriting (MEW) and FDM, and the layered scaffold showed improved performance with significantly larger specific surface area and enhanced cell proliferation, which promote cell adhesion and in vitro osteogenesis compared to the FDM control scaffold.…”
Section: Applications Of 3d Printing In Medical Conditions Associated...mentioning
confidence: 99%